Is the share of renewable electricity in vehicle charging still above the grid mix in Europe? - Sabine Preuß; Robert Kunze; Aline Scherrer; Jakob Zwirnmann; Alexandra Rummel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
Plug-in electric vehicles (PEV) are widely considered a promising option to reduce greenhouse gas (GHG) emissions in transport. The electricity used for charging is decisive for the environmental assessment of PEV. Most studies assume the average grid mix for charging. A study in 2021 showed that the share of renewables in charging electricity of PEV in Europe was above the grid mix. The present study provides an update of this study to further refine the database and to compare the results from 2021 and 2023. In addition, small methodological adjustments were implemented to improve the estimate of renewable electricity in PEV charging across Europe. Therefore, this article presents results of an extensive survey with over 3,400 PEV users in 13 countries across the EU. Results reveal that PEV users still charge their PEV mostly at home. However, the share of renewable charging tariffs for home charging decreased compared to the results from 2021. When considering all charging locations (home, work and public charging), the respective share of renewable contracted electricity, and the number of PEV per EU country, the share of renewables in the charging electricity of PEV has further increased and is still above the European grid mix (i.e., balanced total supplier mix). We discuss reasons for this finding by outlining differences between the results of the study from 2021 and the present one.
Keywords: 330